Paving Walkway Towards the Newly Constructed Toilet. - Ainebyona, Godwin (Kabale University, 2023)
This project helped us to relate the theoretical work and the practical work. The project was carried out at the faculty of Engineering. It was aimed at paving the walkway towards the newly toilet.